Novel Low-Cost Integrated Multiband Antenna Design Customized for Smartwatch Applications with SAR Evaluation. (15th December 2020) - Fady, Brahim; Tribak, Abdelwahed; Terhzaz, Jaouad; Riouch, Fatima
Abstract : This paper presents a novel low-cost integrated multiband antenna design customized for smartwatch applications and wearable devices. The design consists in using a broadband planar patch antenna with circular microstrip lines and a miniaturized feeding-point with a structure of 30 × 30 × 1.6 mm 3, and it is easy to deploy inside the smartwatch and cost-effective for the wearable device industry. The parametric study and final dimensions of the design and the measured results of the reflection and radiation pattern are discussed. The antenna with maximum gain up to 6.6 dBi and S11 up to −22 dB exhibits excellent performance for all the frequencies required in wearable systems such as 1.9 GHz, 2.3 GHz, 2.4 GHz, 2.6 GHz, 5.2 GHz, and 5.8 GHz. We drew a comparison between similar research and this work in terms of antenna performance. Furthermore, we investigate the specific absorption rate (SAR) performance of the antenna for the smartwatch application, using both human hand wrist multilayer and SAM head mouth models. The SAR results in different positions for all the frequencies are compared to the Federal Communication Commission (FCC) standards.